APLICACIÓN DE LA METODOLOGIA SEIS DE SIGMA PARA DISMINUIR LAS DEMORAS EN EL PROCESO DE FACTURACIÓN DE LA CLÍNICA LA MERCED (2013)
Six Sigma is a management system for continuous improvement, which aims to reduce errors and complete customer satisfaction. This management system is employed at Clinica La Merced, focusing on Billing department, supporting administrative processes in order to increase the efficiency of the organization allowing huge profits, always seeking continuous improvement. The goal of Six Sigma is to provide organizations with a 99.99% efficiency, "if it is properly implemented," that because of the advantages and benefits that are achieved when processes are improved in study. To the Clinic La Merced is to implement Six Sigma in order to identify and assess the main cause of the delay in the billing process and identified according to propose improvement actions relevant to the case and thus meet customer requirements.